Effects of Dietary Supplementation with Extruded Linseed on Growth Performance and Meat Quality of Young Holstein Bulls - Stella Dokou; Maria Eleni Filippitzi; Anestis Tsitsos; Vasiliki Papanikolopoulou; Stergios Priskas; Vangelis Economou; Eleftherios Bonos; Ilias Giannenas; Georgios Arsenos (Animals, 2025)
Beef production in Greece is a sector that has been characterized by a decline in both the output and the number of beef-producing animals over the last decades. The major challenge is low beef self-sufficiency; only 19.1% of demand is met by domestic production. The latter leads to a growing reliance on imports of both live animals and carcasses. Hence, the fattening of young bulls from dairy breeds could be an option to address this challenge subject to improving the quality of produced meat. The objective of the present study was to investigate the effects of extruded linseed in the diet of young bulls on their performance and meat quality. Sixty-eight young Holstein bulls were equally assigned in two experimental groups: the control group (CON, n = 34) and Linseed Group (LS, n = 34). Bulls in the CON group received a basal total mixed ration while LS young bulls were offered the same basal ration supplemented with linseed (5% on dry matter basis) during the final fattening stage. All bulls were subjected to three individual weightings at the beginning, the middle and the end of the trial. The feed offered was recorded daily and feed refusals were weighed for each pen to calculate feed intake. After slaughter, the Longissimus dorsi muscle from each carcass was collected to evaluate meat pH, color, chemical composition, tenderness and fatty acid profile. Analysis of variance was used to evaluate the effect of dietary intervention on performance and examined meat parameters, with significance set at p < 0.05, using SPSS software (version 29.0). Average daily gain, dry matter intake and feed conversion ratio were not affected by the dietary intervention (p > 0.05). Similarly, carcass yield and dressing percentage remained unaffected (p > 0.05). Adding extruded linseed did not result in differences in meat quality traits (p > 0.05), except for meat pH, which was significantly decreased in the LS group (p < 0.05), indicating more efficient post-mortem glycolysis. Finally, the inclusion of extruded linseed resulted in higher levels of α-linolenic acid in the meat (p < 0.05). These results suggest that including 5% extruded linseed (on a DM basis) in the diet of young Holstein bulls increased meat n-3 content, improved beef pH and maintained production performance.